IL CASTELLO VISCONTI A SOMMA LOMBARDO - Modello operativo per il rilevamento dei beni culturali - Attilio Selvini (GEOmedia, 2022)
The technique of surveying cultural heritage, like this as in general the topographical one linked to the ground, it profoundly changed between the end of twentieth century and the emergence of the new millennium. Everything has changed, from the measuring instruments to the means of calculation, both by now indissolubly related to electronics and information technology. The present author had the fortune of live all the corresponding transformations either from the operational side as well as from the cultural and research, as a university professor of disciplines geomatics, or topography, photogrammetry and cartography. The latest news, in order of time, is the strong transformation of photogrammetry, which as an auxiliary means for production cartographic as it was born, about a century and half ago, it has now become a multifaceted technique indispensable both in land surveying and cultural heritage.